A return to skiing envelope of function for anterior cruciate ligament reconstructed elite Alpine ski racers - Jordan, M.; Aagaard, P.; Herzog, W, (Science and Skiing VI. 6th International Congress on Science and Skiing, Dec. 14 - 19, 2013, St. Christoph am Arlberg, 2015)
Based on the literature, ski-specific neuromuscular screening is required to help guide the late phase of rehabilitation and return to skiing for the ACLR skier. Screening can be considered conceptually as assessing an envelope of function for ski racing. The first aim of our study was to develop a ski-specific clinical test of functional asymmetry to assess a component of the envelope of function for a ski racer that involves the ability to produce lower-body force during eccentric and concentric movements. We then evaluated functional asymmetry with these tests in a group of actively competing ACLR elite ski racers and uninjured elite ski racers. Due to the importance of hamstrings and quadriceps strength for ski performance and the relationship between ACLR and thigh muscle strength deficits, a second aim was to assess hamstrings and quadriceps explosive strength and maximal strength in uninjured and actively competing ACLR elite Alpine ski racers. We hypothesized that the phase-specific functional asymmetry index in the CMJ and SJ would reveal increased asymmetry in ACLR ski racers compared to uninjured ski racers. We also hypothesized that the injured limb of ACLR ski racers would display significant deficits in hamstrings and quadriceps explosive strength and maximal strength.